A short introduction to promoting resilience in children - Pearce, Colby (JKP short introductions., 2011)
A child's capacity to cope with adversity and 'stand on their own two feet' is seen as critical to their development, well-being, and future independence and success in adulthood. Psychological strength, or resilience, directly affects a child's capacity to cope with adversity. This book provides a succinct, accessible and clear guide on how to promote resilience in children and achieve positive developmental outcomes for them. The author covers three key factors that affect resiliency: vulnerability to stress and anxiety, attachment relationships, and access to basic needs. For each, the auth.